The "privatization" of municipal debt - Ivan T. Ivanov; Tom Zimmermann (University of Cologne, Centre for Financial Research (CFR), 2024)
We study the determinants of local governments' reliance on bank loans using granular data from the Federal Reserve. Governments that are larger, riskier, rely on historically stable revenue sources, or have higher spending relative to revenues are more likely to borrow from banks. Declines in revenues, reductions in bond market access, and relationships with financial advisers and underwriters all strongly predict higher bank loan reliance. While resemblance between bank loans and bonds is limited, loans afford governments significant financial flexibility not otherwise available in the municipal bond market. The frequent loan renegotiation and credit line use are both highly responsive to changes in credit quality, thereby tailoring debt contracts to changes in government fundamentals. The largest entities find this flexibility most useful with nearly 45% of entities in the top revenue quintile obtaining a bank loan by 2017.
Keywords: H74; G21; G32; 330; local government borrowing; debt heterogeneity; fiscal shocks